Final Report: The Effects of Plant Closing or Threat of Plant Closing on the Right of Workers to Organize - Bronfenbrenner, Kate (Cornell University, 1997)
Examines the effects of the sudden plant closings on the principle of freedom of association and the right of workers to organize in the US, Canada, and Mexico.